2016
DOI: 10.1177/1077559516674595
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Risky Sexual Behavior

Abstract: Risky sexual behavior is a serious public health problem. Child sexual abuse is an established risk factor, but other forms of maltreatment appear to elevate risky behavior. The mechanisms by which child maltreatment influence risk are not well understood. This study used data from 859 high-risk youth, followed through age 18. Official reports of each form of maltreatment were coded. At age 16, potential mediators (trauma symptoms and substance use) were assessed. At age 18, risky sexual behavior (more than fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 56 publications
3
32
0
3
Order By: Relevance
“…In a study of 859 high-risk youth (both males and females), those with documented maltreatment reported more risky sexual behaviors in adolescence (Thompson et al, 2017). In a prospective study following 251 adolescents (169 with documented maltreatment) longitudinally, maltreatment was related to subsequent risky sexual behaviors (i.e., ≥4 sexual partners and lack of condom use during last sex) for both males and females in adolescence (Negriff, Schneiderman, & Trickett, 2015).…”
Section: Child Maltreatment and Sexual Risk Behaviorsmentioning
confidence: 97%
“…In a study of 859 high-risk youth (both males and females), those with documented maltreatment reported more risky sexual behaviors in adolescence (Thompson et al, 2017). In a prospective study following 251 adolescents (169 with documented maltreatment) longitudinally, maltreatment was related to subsequent risky sexual behaviors (i.e., ≥4 sexual partners and lack of condom use during last sex) for both males and females in adolescence (Negriff, Schneiderman, & Trickett, 2015).…”
Section: Child Maltreatment and Sexual Risk Behaviorsmentioning
confidence: 97%
“…One item concerning living arrangements was included based on sexual health risks among youth in the care of the state [12]. Three items concern alcohol and drug use: behaviours with a complex but well-established association with sexual risktaking and ill health [3,8,12,[25][26][27]. The inclusion was further motivated by convenience for the youth clinic staff, who are already advised to ask about alcohol and drug use.…”
Section: Sexit Itemsmentioning
confidence: 99%
“…To mention a few, STIs are associated with multiple sexual partners, early sexual debut, alcohol use and experience of transactional sex [2,3]. Experience of sexual violence is associated with unintended pregnancy and STIs through unprotected sex, and a greater likelihood of engaging in transactional sex [4][5][6][7][8]. Engaging in transactional sex is associated with a history of abuse, substance misuse, previous STIs, multiple partners, state care and running away from home [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of child maltreatment and sexual risk behavior have shown that males and females who experienced any kind of sexual abuse had significantly increased odds of engagement in risky sexual behaviors, but a recent study revealed that other forms of maltreatment can increase risky behaviors. Thompson and colleagues [ 138 ] showed that maltreated youths continue to be at high risk for engaging in behaviors that may start a trajectory of problematic sexual behaviors. Clinical and prevention programs should target adolescents with a history of maltreatment and pediatric clinicians have a responsibility to screen at-risk youth for maltreatment experiences.…”
Section: Reviewmentioning
confidence: 99%